Integrated Management In Tissue Cultured Musa Spp. Against Fusarium Wilt Disease Tropical Race 4 (Vcg 01213) - Jason, Heamaashini Nadarajah (2019)
The economic importance of bananas is expressed in valuable foreign revenue through export and also constitutes the economic livelihood of rural households worldwide. The ‘bananageddon’ phenomenon is a term coined to describe the decimation effect of an infamous fungus Fusarium oxysporum f. sp. cubense (Foc) Tropical Race 4 (TR4) that plagues the banana industry globally. The aim of this research was to determine a feasible control strategy in battling Fusarium wilt disease Tropical Race 4 (VCG 01213) through integrated management. Tissue culture materials from four cultivars, namely Berangan Intan (AAA), Grande Naine (AAA), Williams (AAA) and Lemak Manis (AA) were transferred to a Foc hotspot field to determine somaclonal variation through recurrent resistance selection until the plants withered and collapsed or until harvest. HYT Chitinase was applied during planting and also during intervals throughout the growth of the banana plants. Intercropping of banana tissue culture materials with Allium spp. was field tested as well as planted inside potted banana materials prior to field planting to confer disease tolerance. HYT Chitinase was not able to neither induce resistance nor confer tolerance for the four banana cultivars evaluated at the Foc hot spot area. The planting of Allium tuberosum inside the potted banana cultivars prior to field planting did to a certain extent confer tolerance to Berangan Intan cultivar. But, Allium spp. needs to be established for at least 3 generations in a Foc hot spot area in order to obtain negligible levels of Fusarium wilt incidences.